Respuesta :

Answer:

the answer in the attached figure

Step-by-step explanation:

we have

[tex]f(x)=3^{x}[/tex]

The y-intercept of f(x) is the value of f(x) for x equal to zero

so

[tex]f(0)=3^{0}=1[/tex]

Let

[tex]g(x)=f(x)+2[/tex]

substitute

[tex]g(x)=3^{x}+2[/tex]

The y-intercept of g(x) is the value of g(x) for x equal to zero

so

[tex]g(0)=3^{0}+2=3[/tex]

The translation rule is [tex]2[/tex] units up

therefore

the answer in the attached figure

Ver imagen calculista

Answer:

Option D is the correct answer because you simply shift the graph +2 Y

Step-by-step explanation:

ACCESS MORE